Evaluation of Energy Saving and Environmental Protection Effect of Heat Pump for Heating Make-up water for Industrial Boilers - Kien Quoc Vo; Thi Phuong Tuyen Nguyen (Journal of Technical Education Science, 2024)
This paper investigates the integration of heat pumps for heating boiler feedwater and evaluates the impacts of feedwater temperature and condensate recovery rates on fuel consumption, energy efficiency, and CO2 emissions. The results show that using heat pumps significantly reduces boiler fuel consumption, especially when the feedwater temperature increases and the condensate recovery rate is high. In terms of energy, the cost of heat pumps for water heating is significantly lower than that of fuel combustion. With a boiler without condensate recovery, the maximum cost of heat pumps is only about 50% of that of fuel combustion. Economically, heat pumps provide substantial benefits, with maximum cost savings achieved at a water temperature of 75°C. On average, a 10% reduction in the condensate recovery rate, the cost saved in 1 hour is 2000 VND/ton of steam. Additionally, integrating heat pumps reduces CO2 emissions, particularly in boilers without condensate recovery, with the highest emission reduction reaching 17.8 kgCO2/ton of steam. These findings demonstrate that using heat pumps is not only energy-efficient and cost-effective but also contributes to environmental protection by reducing greenhouse gas emissions.